Effect of functional single nucleotide polymorphism g.-572 A > G of apolipoprotein A1 gene on resistance to ketosis in Chinese Holstein cows - Yang, Ling; Bai, Jiachen; Ju, Zhihua; Jiang, Qiang; Wang, Jinpeng; Gao, Yaping; Zhang, Yaran; Wei, Xiaochao; Huang, Jinming (Research in veterinary science, 2021)
The ketosis has negative effects on the high-yielding dairy cows during early lactation. Apolipoprotein A1 (APOA1) is a component of high-density lipoprotein. However, the association of APOA1 gene with ketosis, and the molecular mechanisms of expression of APOA1 gene are not fully understood in dairy cows. In this study, expression of APOA1 in the liver and blood was investigated by RT-qPCR and immunohistochemistry, and genetic variation in the 5′-flanking region of the AOPA1 gene was also screened and identified. In addition, correlation of the single nucleotide polymorphisms (SNPs) of APOA1 gene with blood ketone characters, and activity of APOA1 promoter were analyzed in dairy cows. The results showed that ApoA1 protein was expressed in the liver, and the mRNA level of APOA1 was significantly higher in the cows with ketosis comparing to the healthy cows. In addition, a novel SNP (g.-572 A > G) in the core promoter of the APOA1 gene was identified between base g.-714 and g.-68 through transient transfection in both HepG2 cell and FFb cell, and luciferase report assay. Moreover, there was lower concentration of blood β-hydroxybutyrate in cows with genotype GG comparing to the cows with genotypes AA and AG. This study reported for the first time that the genetic variant g.-572 A > G in the core promoter region of APOA1 gene was associated with the ketosis in Chinese Holstein cows, and g.-572 A > G may be used as a genetic marker for ketosis prevention. •There is an upregulation of APOA1 mRNA in the blood of cows with ketosis comparing to the healthy cows.•A novel SNP (g.-572 A > G) in the core promoter of the APOA1 gene is found.•Concentration of blood β-hydroxybutyrate is related with genotypes of the core promoter of APOA1 gene.